Lipoxin and Aspirin-Triggered Lipoxins. (2010) - Romano, Mario
Abstract : Lipoxins and their 15 epimers, aspirin triggered lipoxins (ATL), are eicosanoids derived from sequential lipoxygenase (LO) metabolism of arachidonic acid. The main routes of lipoxin biosynthesis involve cooperation between 15- and 5-LO, and between 12- and 5-LO. ATL are generated by interactions between 5-LO and aspirin-acetylated cyclooxygenase-2. Cellular models recapitulating these interactions involve leukocytes, platelets, vascular endothelium, and epithelium. To circumvent rapid lipoxin and ATL metabolism and inactivation, stable analogs, bearing potent and long-lasting biological activity, have been synthesized. Some of these analogs displayed therapeutic potential by showing strong anti-inflammatory activity in a number of animal models of disease, including reperfusion injury; arthritis; gastrointestinal, renal, respiratory, and vascular inflammatory disorders; eye damage; periodontitis; and selected infectious diseases. Counter-regulatory signaling by lipoxin A4 and 15-epi-lipoxin A4 is triggered by the activation of a seven-transmembrane domain receptor, termed FPR2/ALX, which is highly expressed in myeloid cells and has been recognized as a main anti-inflammatory receptor.